An honourable calling : political memoirs - Blakeney, Allan (Book collections on Project MUSE., 2008)
As Premier of Saskatchewan from 1971 to 1982, Allan Blakeney played a pivotal role in the shaping of modern Canada. In this engaging and candid political memoir, Blakeney reflects on his four decades of public service, offering first-hand insights on the introduction of government-sponsored medicare, the patriation of the Canadian Constitution, and new approaches to natural resource development. Blakeney provides not only a vibrant picture of the Canadian political landscape, but also vivid portraits of some of Canada's most fascinating political personalities including Pierre Trudeau, Jean Chrétien, René Lévesque, Tommy Douglas, Bill Davis, and Peter Lougheed. He supplies an insider's account of the controversial struggle between the federal and provincial governments as they attempted to reach a compromise in the creation of the Canadian Constitution. Relying on his career-long experience as a medicare advocate, including his work with Tommy Douglas, Blakeney comments on current public medicare issues such as how to finance health care, and the role, if any, of a parallel private system. An Honourable Calling is a thoughtful commentary on many of the central issues in Canadian politics from the last half of the twentieth century and offers perceptive insights into some of the challenges facing Canadians in the decades ahead.